2012
DOI: 10.1186/1752-153x-6-118
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive fluorimetric method for determination of lenalidomide in its bulk form and capsules via derivatization with fluorescamine

Abstract: BackgroundLenalidomide (LND) is a potent novel thalidomide analog which demonstrated remarkable clinical activity in treatment of multiple myeloma disease via a multiple-pathways mechanism. The strong evidences-based clinical success of LND in patients has led to its recent approval by US-FDA under the trade name of Revlimid® capsules by Celgene Corporation. Fluorimetry is a convenient technique for pharmaceutical quality control, however there was a fluorimetric method for determination of LND in its bulk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Calculations on 6 replicate experimental injections, the LOD and LOQ were 0.8 and 2.3 ng/mL respectively, and the relative standard deviations (RSD) did not exceed 2%. The LOD achieved in this method was lower than that achieved in our previous method involving the same derivatization procedure [32]. This is attributed due to the difference in the detection systems between the conventional fluorimeter (in the previous study) and the fluorescence HPLC detector in the method described herein.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Calculations on 6 replicate experimental injections, the LOD and LOQ were 0.8 and 2.3 ng/mL respectively, and the relative standard deviations (RSD) did not exceed 2%. The LOD achieved in this method was lower than that achieved in our previous method involving the same derivatization procedure [32]. This is attributed due to the difference in the detection systems between the conventional fluorimeter (in the previous study) and the fluorescence HPLC detector in the method described herein.…”
Section: Resultsmentioning
confidence: 67%
“…From our previous study of the reaction between LND and FLC [32], we found that the reaction was dependent on FLC concentration, pH of the reaction medium, the nature of the diluting solvent and the duration of the reaction time. The investigations revealed that the best conditions for the reaction were found by maintaining a final concentration of 0.0025% w/v of FLC, a neutral pH using simple water as diluting solvent and leaving the reaction to proceed for five minutes at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Several chromatographic methods including spectrophotometric [12] and fluorimetric [13] methods were developed for the determination of LENA in pharmaceutical formulations such as bulk materials and capsules. Lopez et.…”
Section: Tdmmentioning
confidence: 99%
“…In the past years, fluorescence detection has been proposed as an alternative to mass detectors, but LND is not a fluorescent compound so precolumn derivatization with fluorescamine is necessary, which increases time of procedure and variability. 6,7 On the other hand, none of the published methods has a linearity range that allows therapeutic drug monitoring of LND for pharmacokinetic studies. Accordingly, the development of a new alternative analytical method for the determination of LND in plasma with adequate sensitivity and selectivity, low cost, and wider linearity range is needed.…”
Section: Introductionmentioning
confidence: 99%